Audible children: The sounds of children in medieval miracles - Diesen, Rakel (Collegium Medievale, 2024)
This article aims to unmute medieval children by drawing attention to how their audible presence and participation are reflected in Scandinavian hagiographic sources from the High and Late Middle Ages. The sound-making children discussed here are found in the Nordic hagiographic corpus in Latin, specifically in miracles associated with native Scandinavian saints. These were chiefly written down between the last quarter of the twelfth century and the end of the fifteenth century. This miracle-corpus holds hundreds of narratives featuring children, – child beneficiaries of miracles, the would-be saints as children, and children that feature as helpers, playmates, or siblings. The audible children considered in this article are, however, all children who themselves are said to experience miracles.